2022
DOI: 10.3390/foods11050705
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Antioxidant and Immunoregulatory Activities of a Macromolecular Glycoprotein from Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza has exhibited various bioactive functions due to the existence of polysaccharides, hydrophilic phenolic acids, diterpenoid quinones, and essential oils. However, little research has reported the glycoprotein preparation and corresponding bioactivities. In this study, the water-soluble glycoprotein from S. miltiorrhiza roots was firstly isolated with the extraction process optimized by response surface methodology, and then, the preliminary structural properties, and the antioxidant and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In addition, fucose, galactose hydrochloride, rhamnose, glucosamine hydrochloride, galactose, xylose, mannose, and galacturonic acid were detected in the glycosyl of GUMP. Glycoproteins are normally found in plant leaves such as Azadirachta indica and Camellia sinensis and other food ingredients [ 36 , 37 , 38 ]. Nie et al determined the monosaccharide compositions of green tea glycoprotein and found that galactose was the main component, followed by arabinose [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, fucose, galactose hydrochloride, rhamnose, glucosamine hydrochloride, galactose, xylose, mannose, and galacturonic acid were detected in the glycosyl of GUMP. Glycoproteins are normally found in plant leaves such as Azadirachta indica and Camellia sinensis and other food ingredients [ 36 , 37 , 38 ]. Nie et al determined the monosaccharide compositions of green tea glycoprotein and found that galactose was the main component, followed by arabinose [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nie et al determined the monosaccharide compositions of green tea glycoprotein and found that galactose was the main component, followed by arabinose [ 37 ]. Ji et al [ 38 ] also analyzed the monosaccharide compositions in a glycoprotein they prepared from Salvia miltiorrhiza and demonstrated that its glycoprotein, SMGP, comprised of rhamnose, arabinose, mannose, glucose, and galactose. Thus, the monosaccharide compositions of glycoprotein may be complex and diverse in plants and foods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, bioassay is mostly used for the quality control of macromolecule drugs, including "glycoprotein" drugs, 7 and the molecular weight (Mw) distribution by high-performance gel permeation chromatography with refractive index detector (HPGPC-RID), and the contents of polysaccharides or proteins by UV-VIS have been employed to determine the quality of drugs derived from polysaccharides 8 and/or proteins. 9,10 However, anti-HSV assays should be performed in a strict physical containment level 2 laboratory (P2 lab) owing to the safety considerations; this approach might be practically inapplicable for the routine quality control of PVE30. In addition, the composed monosaccharides/amino acids and their relative contents might also affect the bioactivity of "glycoprotein" drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite salvia glycoproteins can increase the activity of antioxidant enzymes and reduce malondialdehyde (MDA) levels, the potential mechanism remains unknown. Therefore, it is meaningful to study this mechanism at the cellular level [ 22 ].…”
Section: Introductionmentioning
confidence: 99%